A doll's house - Ibsen, Henrik; Rafferty, Mary. (Cambridge : Cambridge University Press, 2000)
Ibsen's seminal play, which changed modern drama, is a searing view of a male-dominated and authoritarian society, presented with a realism that elevates theatre to a level above mere entertainment. The reverberations of Nora's slamming the door as she leaves Torvald continue to the present day
Includes references.
Keywords: Drama; Electronic books; Man-woman relationships